Spinodal Decomposition-Driven Structural Hierarchy of Mesoporous Inorganic Materials for Energy Applications - Ban, Minkyeong; Woo, Dongyoon; Hwang, Jongkook; Kim, Seongseop; Lee, Jinwoo (Accounts of Chemical Research, 2023)
Conspectus Mesoporous inorganic materials (MIMs) directed by block copolymers (BCPs) have attracted tremendous attention due to their high surface area, large pore volume, and tunable pore size. The structural hierarchy of inorganic materials with designed meso- and macrostructures combines the benefits of mesoporosity and tailored macrostructures in which macropores have increased ion/mass transfer and large capacity to carry guest material and have a macroscale particle morphology that permits close packing and a low surface energy. Existing methods for hierarchically structured MIMs require complicated multistep procedures including preparation of sacrificial macrotemplates (e.g., foams and colloidal spheres). Despite considerable efforts to control the macrostructures of mesoporous materials, major challenges remain in the formation of a structural hierarchy with ordered mesoporosity. In polymer science, spinodal decomposition (SD) is a physical phenomenon that spontaneously produces a wide variety of macroscale heterostructures from interconnected networks to isolated droplets. Exploitation of SD is a promising method to achieve precise control of the macrostructure (e.g., macropore, particle morphology) and mesostructure (e.g., pore size and structure, composition) of inorganic materials. However, this approach for tailoring the structural hierarchy of MIMs is unexplored due to the lack of effective systems that can control the complex thermodynamic interactions of inorganic precursor/polymer blends and the phase-separation kinetics. In this Account, we present our recent research progress on the development of synthesis systems that combine unique SD behaviors and BCP self-assembly in polymer blends. To generate macropores in MIMs, we have exploited interconnected macrostructures of SD induced by designed quench conditions of multicomponent blends containing BCP. These strategies enable control of the size of the macropores of the nanostructures independently and can be extended to various compositions (e.g., carbon, SiO2, TiO2, WO3, TiNb2O7, TiN). We also control the macroscopic morphology of the MIMs into spherical particles (e.g., solid and hollow mesoporous spheres) by using SD induced by increasing the mixing entropy penalty of polymer blends that consist BCP, homopolymer(s), and inorganic precursors. Furthermore, interfacial tension between polymers determines the macroscopic morphology of MIMs, from isotropic to anisotropic mesoporous particles (e.g., oblate, bowl, 2D nanosheet). The interfacial states of the homopolymer determine the pore orientation and particle morphology of BCP-directed MIMs. We also highlight the application of the hierarchically structured MIMs in energy storage devices. Generated macropores facilitate ion/mass transfer in lithium-ion batteries and stable accommodation of a large amount of sulfur in lithium-sulfur batteries. Designed morphologies of MIMs are beneficial to achieve high packing density as electrode materials in potassium-ion batteries and thereby achieve high volumetric capacities. Recent advances in SD-driven synthesis for the structural hierarchy of MIMs will inspire how polymer science can be used as a platform for preparing the designed inorganic materials. Additionally, broadening the polymer and composition repertoire will guide in novel frontiers in the design and applications of MIMs in various fields.